DIFFERNERT CHANGES THAT WOMEN MAY OCCUR DURING THEIR PREGNANCY - Kodirova Zebiniso Nuridullaevna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, the vitamins needed for proper fetal development pass through the mother's body, if the mother is healthy, there are no birth defects, the fetus develops normally, the serous fluid in the pelvic joints softens, the mother's body and growing fetus need more water and so on.